Innovative Ergonomic Solutions: Integrating 3D-CAD, Virtual Reality, and Mixed Methods for Railway Maintenance Workers - Akuma, Hellstrome Young; Abdullah, Nazlin Hanie (Journal of Industrial Engineering and Halal Industries, 2025)
Physical ergonomics is critical in safeguarding worker safety and well-being, particularly in demanding work environments such as maintenance tasks involving complex engineering systems (CES). The ergonomics field is evolving with new technological tools, offering innovative approaches to enhance current assessment protocols. This study proposes a conceptual framework integrating advanced technological tools, specifically, Three-Dimensional Computer-Aided Design (3D-CAD) and Virtual Reality (VR), with conventional mixed methods approaches to optimize ergonomic solutions for railway maintenance workers. The proposed framework combines quantitative data, such as anthropometric measurements and workstation evaluations, with qualitative insights from worker feedback, ensuring a holistic approach to ergonomic assessment. By incorporating VR technology, the framework creates an immersive environment where workers can interact with full-scale models of their workstations, providing detailed feedback essential for both proactive and corrective ergonomic interventions. The study demonstrates that this integrated approach effectively addresses ergonomic challenges by merging the objectivity of quantitative analysis with the contextual depth of qualitative insights. The findings suggest that the proposed framework enhances worker performance and safety and supports continuous improvement in ergonomic practices. The study concludes that this framework is valuable for comprehensive research into ergonomic challenges in railway maintenance and offers a versatile methodology for improving worker well-being in similar high-risk industries.